Mental health state and its determinants in German university students across the COVID-19 pandemic: findings from three repeated cross-sectional surveys between 2019 and 2021 - Angeliki Tsiouris; Antonia M. Werner; Antonia M. Werner; Ana N. Tibubos; Ana N. Tibubos; Lina M. Mülder; Jennifer L. Reichel; Sebastian Heller; Markus Schäfer; Lisa Schwab; Thomas Rigotti; Thomas Rigotti; et al. (Frontiers Media S.A., 2023)
BackgroundStudents were at an increased risk for elevated mental symptoms during the first year of the COVID-19 pandemic compared to pre-pandemic levels. As universities remained closed much longer than anticipated, the mental burden was expected to persist through the second year of the pandemic. The current study aimed to investigate the prevalence of mental distress from 2019 through 2021 and identify risk factors for elevated mental burden, focusing on gender.MethodsWe analyzed three cross-sectional online surveys among students at the University of Mainz, conducted in 2019 (n = 4,351), 2020 (n = 3,066), and 2021 (n = 1,438). Changes in the prevalence of depressive symptoms, anxiety, suicidal ideation, and loneliness were calculated using Pearson's chi-square tests and analyses of variance. Multiple linear regressions yielded associated risk factors.ResultsThe proportion of students with clinically relevant depressive symptoms was significantly higher during the pandemic (38.9% in 2020, and 40.7% in 2021), compared to pre-pandemic (29.0% in 2019). Similarly, more students reported suicidal ideation and generalized anxiety during the pandemic with a peak in the second pandemic year (2021). The level of loneliness was significantly higher in 2020, compared to 2019, and remained at a high level in 2021 (p < 0.001, ηp2 = 0.142). Female and diverse/open gender, being single, living alone, and being a first-year student were identified as risk factors associated with mental burden during the pandemic.DiscussionMental burdens remained elevated among students through the second year of the pandemic and were associated with socio-demographic risk factors and pandemic-related concerns. Future research should monitor recovery and evaluate the need for psychosocial support.